Family Photography as Object and Practice in Independent Comics in Indonesia - Terra Bajraghosa; Budi Irawanto; Seno Gumira Ajidarma (IJCAS (International Journal of Creative and Arts Studies), 2023)
One small element that is rarely put in the comics’ scene setting is photographic imagery, commonly a portrait of a person or a family photograph. It is assumed that once a family photograph is presented in a comic, it definitely has a particular function. This study will examine how the family photograph as an object and practice is depicted and present the signification of the story meaning in independent comics. The research object is a drawing that represents a family photograph in a panel, or series of panels – consecutive or non-consecutive -in the independent comic "Pupus Putus Sekolah" (2022) and “Phagia” (2016) as the case study. This research uses a comic studies approach based on qualitative methods. The first analysis process is to pay attention to the presence of family photographic images in comic stories. In the following analysis stage, family photographs are treated as an object defined by social practices based on a semiological/discursive approach, especially the Doing Family Photography approach introduced by Gillian Rose. The study revealed that photographic images in independent comics were shown using the same artistic drawing style as the characters and objects in the story. The inclusion of family photographs in comics aims to present a portrayal of the 'evidence,' 'truth,' and 'indexicality' as the genuine authenticity of the photographed moments in photography while also serving as a symbolic picture in storytelling. The readers' comprehension of the indexical nature of the family photograph is inherently linked to the manner in which the photographic imagery is portrayed and organized with other elements in the sequential composition of comics.Foto Keluarga sebagai Objek dan Praktik dalam Komik Independen di Indonesia Abstrak Salah satu elemen kecil yang jarang dimasukkan ke dalam adegan komik adalah citra fotografi, biasanya potret seseorang atau foto keluarga. Diasumsikan jika foto keluarga disajikan dalam komik, pasti memiliki fungsi tertentu. Penelitian ini akan mengkaji bagaimana foto keluarga sebagai objek dan praktik digambarkan dan menyajikan signifikasi makna cerita dalam komik independen. Objek penelitian adalah gambar yang merepresentasikan foto keluarga dalam sebuah panel, atau rangkaian panel—berurutan atau tidak berurutan—dalam komik independen "Pupus Putus Sekolah" (2022) dan "Phagia" (2016) sebagai studi kasus. Penelitian ini menggunakan pendekatan studi komik berdasarkan metode kualitatif. Tahap analisis pertama adalah memperhatikan citra fotografi keluarga dalam cerita komik. Pada tahap analisis berikutnya, foto keluarga diperlakukan sebagai objek yang didefinisikan oleh praktik sosial, berdasarkan pendekatan semiologis/diskursif, terutama pendekatan Doing Family Photography yang diperkenalkan oleh Gillian Rose. Studi ini mengungkapkan bahwa gambar fotografi dalam komik independen ditampilkan menggunakan gaya gambar yang sama dengan karakter dan objek dalam cerita. Pencantuman foto keluarga dalam komik bertujuan untuk menyajikan penggambaran 'bukti', 'kebenaran', dan 'indeksikal' sebagai keaslian asli dari momen yang difoto dalam fotografi sekaligus berfungsi sebagai gambaran simbolis dalam bercerita. Pemahaman pembaca tentang sifat indeksikal foto keluarga secara inheren terkait dengan cara di mana citra fotografi digambarkan dan diatur dengan unsur-unsur lain dalam komposisi komik yang berurutan.